2013
DOI: 10.1038/bjc.2013.95
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of a nomogram for prediction of lymph-node metastasis detected with conventional histopathology and ultrastaging in endometrial cancer

Abstract: Background:We developed a nomogram based on five clinical and pathological characteristics to predict lymph-node (LN) metastasis with a high concordance probability in endometrial cancer. Sentinel LN (SLN) biopsy has been suggested as a compromise between systematic lymphadenectomy and no dissection in patients with low-risk endometrial cancer.Methods:Patients with stage I–II endometrial cancer had pelvic SLN and systematic pelvic-node dissection. All LNs were histopathologically examined, and the SLNs were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 25 publications
(39 reference statements)
0
14
0
3
Order By: Relevance
“…Eleven studies were excluded because of subsequent more comprehensive publications on the same database. One exception was Koskas et al [21], which included patients from the landmark SENTI-ENDO paper [22]. We chose to exclude the more recent and larger study because the outcome measures of interest in our review were more comprehensively reported in SENTI-ENDO.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies were excluded because of subsequent more comprehensive publications on the same database. One exception was Koskas et al [21], which included patients from the landmark SENTI-ENDO paper [22]. We chose to exclude the more recent and larger study because the outcome measures of interest in our review were more comprehensively reported in SENTI-ENDO.…”
Section: Resultsmentioning
confidence: 99%
“…The low sensitivity of PET/CT for determining lymph-node metastasis in endometrial cancer patients is the main shortcoming of this test as a diagnostic tool [15]. Omitting patients who need lymphadenectomy carries a risk of inadequate staging, leading to secondary lymphadenectomy or systematic adjuvant radiotherapy [18]. Discrepancy rates have been stated as up to 33% in some studies [19].…”
Section: Discussionmentioning
confidence: 99%
“…All patients fasted for at least 6 hours before the PET/CT imaging. 18 F-FDG (3.7 MBq/kg body weight) was administered antecubitally. After a 60-90-minute uptake period, whole-body PET/CT was performed.…”
Section: Imaging Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of such "low-volume, ultrastage-detected LN metastases" has been reported to be around 5% and interestingly, in such patients, the rate of micrometastases and isolated tumor cells does not seem to be correlated with myometrial invasion 99 and primary tumoral aggressiveness 100 . However, the oncologic significance of "low volume LN metastases" has not been reported yet.…”
Section: Sentinel Lymph Node (Sln) Biopsymentioning
confidence: 99%